Evaluation of the oral health of schoolchildren in Monte Formoso, Minas Gerais: cross-sectional study - Gomes Luiz, Brunno Emanuel; Cardoso Neves, Edwin; Seixas Mourão, Priscila; Ramos Glória, José Cristiano; Gonçalves Gusmão, Yure; Douglas de Oliveira, Dhelfeson Willya (Revista Estomatología, 2026)
Background: Dental caries in childhood remains an important public health issue, strongly influenced by socioeconomic conditions and access to health services. Local epidemiological studies are essential to guide preventive strategies and oral health public policies. Objective: To analyze the oral health of schoolchildren in Monte Formoso, Minas Gerais, Brazil, and evaluate the correlation between dental caries and socioeconomic factors, comparing urban and rural areas, as well as 5- and 12-year-old children. Materials and methods: A cross-sectional study was conducted with 132 children (aged 5 and 12) enrolled in public schools. The DMFT and deft indices were assessed, and guardians completed questionnaires on socioeconomic and health-related data. Data were analyzed using the Mann-Whitney test for group comparisons and Spearman’s correlation for associations between variables. A significance level of p<0.05 was adopted. Results: The deft index was 2.17 for 5-year-olds and 1.76 for 12-year-olds. The decayed component was 7.8% in younger children and 4.1% in 12-year-olds. A significant negative correlation was found between income and the deft index. Children who had visited a dentist had a higher deft/DMFT index (2.03). No significant differences in caries indices were observed between age groups or between urban and rural areas. Conclusion: Monte Formoso presents low deft and DMFT indices in both 5- and 12-year-old children, with no significant variations by age or area of residence.